Letter - Kingston, Charles Cameron, 1850-1908. (1898)
Letter to Archibald of the Bulletin, Premiers Office, Adelaide, South Australia.
Manuscript reference no. : NLA MS 962.
Premiers of South Australia.
Keywords: Kingston, Charles Cameron, -- 1850-1908 -- Correspondence; Politicians -- South Australia -- Correspondence; State politicians